STRATEGI MARKETING ISU OLEH PARTAI DEMOKRASI INDONESIA – PERJUANGAN(PDI-P) DALAM PEMENANGAN JOKO WIDODO- MUHAMMAD JUSUF KALLA PADA PEMILIHAN PRESIDEN DI KABUPATEN TAPANULI UTARA TAHUN 2014 - Daniel Pardamean Hutagalung; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research arms to observe the victory Joko widodo- Jusuf Kalla in the 2014 President Elections North Tapanuli District and this Study focusing on Marketing Strategy Issues which is conducted by Indonesian Democratic Party-Struggle and the Winning team of Joko Widodo- Jusuf Kalla in North Tapanuli District. And this Marketing Strategy which is the conducted by the struggle of the democratic party and the winning team of Joko Widodo-Jusuf Kalla in North Tapanuli District.This Study used qualitative methods and Methods of Phenomonology then for descriptive analysis of the data presented in the form qualitative describe in detail the actual situation and by looking at the actual problems and goals research.Reseach conducted by the problem of research into information objects which aims to achieve the objectives and the information in this study.The result showed in pursuing a strategy to obtain high sound in the North Tapanuli District conduted by Indonesian Democratic Party-Struggle in the presidensial election 2014. Marketing Strategy Issues where the winning team to package the issues that are relevant to the condition in the North Tapanuli District. Many Issues that attractive Voters. Ranging agricultural issues, Education Issues, Health Care Issues, the issues of the Religion and ethnicity. This issues was considered appropriate and relevant to the condition in the North Tapanuli District.Key Words:Strategy, Political Marketing , Political Party